2020
DOI: 10.1038/s41467-020-15066-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia induces glutamine-fuelled anaplerosis in retinal Müller cells

Abstract: Although supplemental oxygen is required to promote survival of severely premature infants, hyperoxia is simultaneously harmful to premature developing tissues such as in the retina.Here we report the effect of hyperoxia on central carbon metabolism in primary mouse Müller glial cells and a human Müller glia cell line (M10-M1 cells). We found decreased flux from glycolysis entering the tricarboxylic acid cycle in Müller cells accompanied by increased glutamine consumption in response to hyperoxia. In hyperoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…HIF-1α (#QT01039542) and VEGF (#QT00160769) were analyzed using primers from Qiagen. Primers for all other genes investigated are listed in the Gas Chromatograpy-Mass Spectrometry: As previously described (Singh et al, 2020), for each mouse, both retinas were dissected on ice cold HBSS and flash frozen. To each tube, 500 µl of -20°C 80% methanol was added with 20 µl of 0.05 mg/ml of [ 13 C5] ribitol as internal standard.…”
Section: Genotypingmentioning
confidence: 99%
“…HIF-1α (#QT01039542) and VEGF (#QT00160769) were analyzed using primers from Qiagen. Primers for all other genes investigated are listed in the Gas Chromatograpy-Mass Spectrometry: As previously described (Singh et al, 2020), for each mouse, both retinas were dissected on ice cold HBSS and flash frozen. To each tube, 500 µl of -20°C 80% methanol was added with 20 µl of 0.05 mg/ml of [ 13 C5] ribitol as internal standard.…”
Section: Genotypingmentioning
confidence: 99%
“…Biomass synthesis pathways like serine/one-carbon and glutaminolysis involve Myc protein. These pathways were found to be altered by hyperoxia in our previous studies (Singh et al, 2019;Singh et al, 2018;Singh et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
“…Six-hundred microliters of supernatant was transferred to fresh tubes and dried under vacuum in a -4°C cold vacuum evaporator (Labconco). Samples were derivatized with the two step protocol as described earlier (Singh et. al.…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…We have evaluated the strategy of stabilizing HIF during hyperoxia using protection against vascular obliteration and pathological angiogenesis measured in retinal flatmounts as one metric of efficacy. In retinas protected against retinopathy we find (1) no liver or kidney toxicity, (2) 85-100% reduction of oxygen induced retinal vasoobliteration and neovascularization in mice and rats, (3) normalization of the electroretinogram in hyperoxia, (4) normalization of ocular coherence tomography, (5) a cadre of serum biomarkers secreted by liver, and (6) and a metabolic switch to upregulate the urea cycle and 1C/serine metabolism (Hoppe et al, 2014(Hoppe et al, , 2016Singh et al, 2019Singh et al, , 2020. We observed that when using DMOG, hepatic HIF-1 was necessary and sufficient to prevent OIR but that Roxadustat could partially overcome hepatic HIF-1 ablation because it also targeted the retina.…”
Section: Introductionmentioning
confidence: 87%